KEMUNGKINAN PENGGUNAAN LATEX UNTUK STABILISASI BADAN JALAN HUTAN - Rahardjo S Suparto; S Sutopo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
Among the many known stabilized methods and materials that can be applied to improve forest road stability, latex is thought of as one such material that deserves trying. This experiment is to asses the possibility of using latex as a stabilizing agent,The fol/owing conclusions are in order: Latex can be used as stabilizing agent for clayey soils as subgrade material. A 4% latex content turned out to be effective to keep swelling, due to soaking in water, within a limit of 4,3%. Degree of compaction has no significant effect of swell. Degree of compaction and percentage of latex content has significant effect on bearing capacity. Latex may be recommended as an alternative material for stabilizing subgrade soil in forest road construction.